A Planar, Conjugated N4‐Macrocyclic Cobalt Complex for Heterogeneous Electrocatalytic CO2 Reduction with High Activity. Issue 39 (4th August 2020) - Sun, Libo; Huang, Zhenfeng; Reddu, Vikas; Su, Tan; Fisher, Adrian C.; Wang, Xin
Abstract: Metal complexes have been widely investigated as promising electrocatalysts for CO2 reduction. Most of the current research efforts focus mainly on ligands based on pyrrole subunits, and the reported activities are still far from satisfactory. A novel planar and conjugated N4 ‐macrocyclic cobalt complex (Co(II)CPY) derived from phenanthroline subunits is prepared herein, and it delivers high activity for heterogeneous CO2 electrocatalysis to CO in aqueous media, and outperforms most of the metal complexes reported so far. At a molar loading of 5.93×10 −8 mol cm −2, it exhibits a Faradaic efficiency of 96 % and a turnover frequency of 9.59 s −1 towards CO at −0.70 V vs. RHE. The unraveling of electronic structural features suggests that a synergistic effect between the ligand and cobalt in Co(II)CPY plays a critical role in boosting its activity. As a result, the free energy difference for the formation of *COOH is lower than that with cobalt porphyrin, thus leading to enhanced CO production. Abstract : Heterogeneous CO2 reduction with a novel planar and conjugated N4 ‐macrocyclic metal complex of Co(II)CPY/CNT was investigated. Systematic investigation in aqueous electrolyte shows it has high activity and outperforms most metal complexes reported so far.